Is combined myocardial performance index and tricuspid annular plane systolic excursion a better predictive estimator than each of them alone in patients with inferior ST-elevation myocardial infarction? - Hamlet Grigori Hayrapetyan; Karlen Grigori Adamyan; Inna Arshavir Arakelyan (KARE Publishing, 2014)
Objectives: We aimed to assess the combined estimator of left ventricular (LV) myocardial performance index (MPI) and tricuspid annular plane systolic excursion (TAPSE) as a pooled independent predictive factor for hospital mortality and one-year mortality and re-hospitalization in patients with primary LV inferior ST segment elevation myocardial infarction (STEMI). Study design: We prospectively studied 221 consecutive patients (189 males, 32 females; mean age 58.2+-4.5; range 38 to 72 years) with primary LV inferior STEMI. Standard echocardiography and Doppler myocardial imaging were used within 24 hours of onset of myocardial infarction to measure LV MPI and TAPSE. Based on LV MPI and TAPSE values, all subjects were categorized into two groups: Group 1 with LV MPI ≥0.55 and TAPSE ≤14 mm (n=78) and Group 2 with the remaining patients (n=143). Patients were followed up for the endpoints of hospital mortality, one-year mortality and oneyear re-hospitalization. Results: Hospital mortality (17.9% vs. 6.3%, adjusted odds ratio [ORadj] 3.26, p<0.01) one-year mortality (39.1% vs. 14.2%, ORadj 3.88, p<0.001) and one-year re-hospitalization rates (50.0% vs. 18.7%, ORadj 4.36, p<0.001) were significantly higher in Group 1 than in Group 2. Compared with OR for LV MPI ≥0.55 vs. LV MPI <0.55 or TAPSE ≤14 mm vs. TAPSE >14 mm alone, the pooled parameter of LV MPI ≥0.55 and TAPSE ≤14 mm was shown to be the better predictive estimator, with higher OR and lower significance p-values. Conclusion: In primary LV inferior STEMI patients, combined LV MPI ≥0.55 and TAPSE ≤14 mm was seen to be a more valuable prognostic estimator than LV MPI ≥0.55 or TAPSE ≤14 mm alone for stratifying risky patients.